1994
DOI: 10.1093/nar/22.23.4890
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and equilibrium binding studies of the human papillomavirus type-16 transcription regulatory protein E2 interacting with core enhancer elements

Abstract: The human papillomaviruses (HPVs) are a family of DNA viruses which cause benign tumours of the skin and mucosa that infrequently progress to malignant carcinoma. The E2 open reading frame of HPV is thought to encode a papillomavirus-specific transcription factor which also has a role in viral replication. The E2 proteins of all papillomaviruses studied to date have been shown to bind specifically to the common conserved sequence ACC(N)6GGT found at multiple locations in their genomes. In the case of HPV-16, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 45 publications
6
45
0
Order By: Relevance
“…We have shown that mutations at these positions can significantly reduce the binding of hE2. These results confirm and extend the previous observation that a change from A:T to C:G at this position weakens the binding of the hE2 C-terminal domain (29). In contrast, the consensus bE2-binding site shows no preference for A:T at position 7 and a change from A:T to C:G at this position has been shown to result in a slight increase in the binding of bE2 (8).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have shown that mutations at these positions can significantly reduce the binding of hE2. These results confirm and extend the previous observation that a change from A:T to C:G at this position weakens the binding of the hE2 C-terminal domain (29). In contrast, the consensus bE2-binding site shows no preference for A:T at position 7 and a change from A:T to C:G at this position has been shown to result in a slight increase in the binding of bE2 (8).…”
Section: Discussionsupporting
confidence: 90%
“…As amino acids outside this C-terminal region could form important contacts with the DNA we have used the full-length protein to determine relative dissociation constants for the interaction of hE2 with these sites. The values obtained for the full-length protein are similar to those which have previously been obtained using the isolated C-terminal domain (29). This suggests that, unlike the EBNA1 core domain, the hE2 C-terminal domain is the sole determinant of DNA binding affinity and specificity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The extremely slow half-time for dissociation (Ͼ4 h, see Ref. 9) and the very high stability of the E2-DNA complex suggests a quasi-irreversible reaction, with strong implications for its mechanism of action. The conditions under which the dissociation rate was measured include a number of additions to the buffer, including 10% glycerol; these may affect the stability and therefore the off-rate.…”
Section: Discussionmentioning
confidence: 99%
“…The protein consists of a C-terminal DNA-binding and dimerization domain (E2-DBD) 1 and an N-terminal transactivation domain, separated by a flexible region (8). The E2-DBD is an ϳ80-residue per monomer domain that can be overexpressed recombinantly in bacteria as a stable and soluble dimer (9,10). Its biological importance is shown by the three forms of the protein produced by alternative splicing: the full-length protein (E2-TA), which acts as a transcriptional activator, and two shorter forms (E2-TR and E2/E8) produced from alternative splicing, acting as repressors (11).…”
mentioning
confidence: 99%